The Educational motive for Righteous Families in the Holy Qur’an (Islamic Sciences Journal, 2023)
This research deals with the righteous families in the Holy Qur’an. The Noble Qur’an has told us examples of multiple families represented by the families of the Prophets, peace be upon them and others. We have shown in this research the attitudes, judgment, and educational images that these families took in building their good families, and how these families established the moral criterion.  In light of a continuous commitment from the two corners of the family to the children, where children acquire morals and principles, and are nourished by the culture that guides them in their future behavior.
Keywords: the righteous families, the prophets, family, children.